Pedestrian Safety in Dhaka Mega City of Bangladesh: Behaviour, Attitude and Risk Perception (Journal of Engineering Science, 2023)
Pedestrians are always the most vulnerable road victims in terms of crash involvement. In low-motorized developing countries like Bangladesh, this problem is disproportionately higher, particularly in an urban setting. Therefore, there is a need to develop a pragmatic strategy to arrest this problem with a proper understanding of their behavior, attitude, and perception. In this study, an attempt has been made to evaluate the risk perception, attitude, and behavior of pedestrians. A comprehensive questionnaire survey enabled the collection of pedestrian behavior, attitude, and risk perception data, which included different categories of users. From this analysis, it is evident that perception and attitude are closely related, and in most cases that is very positive. However, there is a huge gap between perception, attitude, and behavior. Many respondents have proven their accurate feelings, right understanding, or belief, but their behavior represents differently. The paper elaborates on these two confronting issues with the evidence and concludes with potential implications for improving pedestrian safety.Journal of Engineering Science 13(2), 2022, 117-125